A Brief Review of Extensor Tendon Injuries Specific to the Pediatric Patient. (March 2015) - Dwyer, C. Liam; Ramirez, Rey N.; Lubahn, John D.
Extensor tendon injuries in the pediatric population require careful evaluation and treatment. This article focuses on the differences in injury type and treatment of pediatric versus adult extensor tendon injuries. A detailed history and physical examination is crucial in the management of extensor tendon injuries of the young patient. Treatment of pediatric extensor tendon injuries depends largely on the site of injury. A majority of these injuries may be treated with splinting or primary repair. Treatment methods that require high compliance must be adjusted for the young child.